Inheritance of Spot Blotch Disease Components in Barley. Issue 5 (2nd September 2016) - Singh, Tejveer; Mishra, Vinod Kumar; Chand, Ramesh
ABSTRACT: A large environmental influence on phenotypic estimates of spot blotch (SB) resistance and the complex polygenic nature of SB resistance in barley ( Hordeum vulgare L.) are a limitation to developing resistant cultivars. Component-based polygenic resistance would help in selecting lines with durable resistance. The objective of this research was to investigate the genetics of three important components of resistance to spot blotch caused by Bipolaris sorokiniana (Sacc.) Shoemaker. A total of 124 genotypes were evaluated and two most diverse genotypes each for latent period (LP), number of lesions (NL), and spore production (SP) were selected. To determine the inheritance of LP, NL, and SP, selected diverse genotypes were crossed and advanced to F2, F3, and F4 generations. Inheritance pattern indicated that LP was controlled by 2–3 effective genes, whereas NL and SP were controlled by three genes each. Across the segregating generations, SP and NL showed positive (r = 0.68–0.82) and LP showed negative (r = −0.78–−0.88) association with area under disease progress curve (AUDPC). Narrow-sense heritability estimated by regression of F4 progenies on F3 generation was 0.81 for LP, 0.78 for NL and 0.67 for SP. Transgressive segregants were observed for latency period in all segregating generations. These results should help in the development of durable resistance against spot blotch. Identified transgressive segregants for spot blotch resistance could be utilized directly as cultivars after multilocation/multienvironment evaluation and/or could be used as donors to introgress spot blotch resistance into other improved backgrounds.